Adapted and validated psychological health scale in the doctoral context - Vincent, Cynthia; Plante, Isabelle; Tremblay-Wragg, Émilie; Barroso da Costa, Carla (Mesure et évaluation en éducation)

(untitled) (ADMEE-Canada, 2022)
Despite the growing number of studies on the psychological health of doctoral students, interest seems to be focused on their psychological distress. This may be due to the lack of available tools contextualized to doctoral work to measure both psychological distress and well-being, which represent two indissociable aspects of psychological health. Since such a tool appears essential for future empirical research that will attempt, for example, to clarify the predictors and consequences of this construct, the present study aimed to adapt an existing work- related psychological health scale (Gilbert et al., 2011) into a short, doctoral- contextualized version, and to examine its psychometric qualities. Four indicators of construct validity (exploratory, confirmatory, convergent, and predictive) and two indicators of reliability (internal consistency and temporal stability) were examined among two samples including 380 and 377 doctoral students, respectively. A short unidimensional scale comprising eight items (four items measuring the distress pole and four items measuring the well-being pole) with good psychometric qualities was obtained, supporting its use in future studies.